Action-research in times of pandemic: experiences in a professional master's program (Revista Internacional de Formação de Professores, 2023)
The methodological path carried out in a professional master's research developed in the covid-19 pandemic is presented. Interviews were carried out with artisanal fishermen, conversation circles with teachers of the Fishing course at IFCE and the production of a documentary. The field research was interrupted due to the pandemic, being resumed after revisions in the methodology, without changes in the objectives. The documentary images were produced by the fishermen with their cell phones and the debate with the teachers took place in a remote format. It is concluded that every investigation is subject to uncertainties and that the researcher must be creative to overcome obstacles.
Keywords: Professional master; Educational product; Action-research; Pandemic; Artisanal fishing